Evaluasi Pendidikan Agama Islam (PAI) Berbasis Digital - Rahmat; Zulkifli Musthan; Abd. Kadir; Muh, Shaleh; Anirwan; Halik (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Digital transformation in education requires changes in learning assessment approaches, including in Islamic Religious Education (PAI). This article aims to analyze the concepts, urgency, approaches, and implementation of digital-based PAI assessment and its implications for improving learning quality. This study employs a literature review method by examining and analyzing relevant scholarly literature on educational assessment, digital technology, and PAI learning. The findings indicate that digital-based PAI assessment not only improves the efficiency, flexibility, objectivity, and transparency of assessment but also enables continuous evaluation through the utilization of learning data and students’ learning traces. The review also reveals that the effectiveness of digital assessment remains constrained by limited infrastructure, unequal access, digital literacy gaps, and risks related to academic ethics and integrity. In the context of PAI, the use of technology must preserve spiritual, character-building, and humanistic dimensions. Therefore, a blended assessment approach offers a strategic alternative by integrating the advantages of digital technology with pedagogical interaction and the continuous cultivation of Islamic values.